2007
DOI: 10.1108/07363760710720975
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitudes toward counterfeits: a review and extension

Abstract: PurposeThe purpose of this research is to propose and test a model that integrates the main predictors of consumers' attitude and behavioral intentions toward counterfeits; to help companies understand the main factors influencing consumer behavior toward counterfeits and create effective anti‐piracy strategies.Design/methodology/approachAn integrated model is proposed following the studies by Ang et al. and Huang et al. A survey with 400 consumers was conducted in the Brazilian market and the Structural Equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(94 citation statements)
references
References 25 publications
8
85
1
Order By: Relevance
“…Ang et al (2001) found a negative effect of integrity to favorable attitudes toward counterfeits. Matos et al (2007) also found the reverse impact of integrity to favorable attitudes toward counterfeits of consumers in Brazil. Consumers have integrity is as high as it had favorable attitudes toward counterfeits ).…”
Section: Integrity and Attitudesmentioning
confidence: 99%
See 3 more Smart Citations
“…Ang et al (2001) found a negative effect of integrity to favorable attitudes toward counterfeits. Matos et al (2007) also found the reverse impact of integrity to favorable attitudes toward counterfeits of consumers in Brazil. Consumers have integrity is as high as it had favorable attitudes toward counterfeits ).…”
Section: Integrity and Attitudesmentioning
confidence: 99%
“…So the attitudestoward counterfeit goods is an vital factor to predict the intention of buying counterfeit goods, especially for luxurious fashion brands (Nordin, 2009). There is a positive relationship between favorable attitudes and intention to purchase toward counterfeiting goods (Ang et al 2001;Huang et al, 2004;Matos et al, 2007;Nguyen & Tran, 2013 …”
Section: Attitudes and Intention To Purchase Toward Counterfeiting Lumentioning
confidence: 99%
See 2 more Smart Citations
“…Attitudes towards behavior instead of towards the product are important to be a better predictor of behavior (Phau and Teah, 2009;Penz and Stottinger, 2005). Several studies found that attitudes towards counterfeit products plays an important positive influence to purchase intention (Phau and Teah, 2009;Nordin, 2009;De Matos et al, 2007; www.ccsenet.org/ijms International Journal of Marketing Studies Vol. 5, No.…”
Section: Purchase Intention -Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%